Development of auto re-closer earth leakage circuit breaker for domestic appliances - Muhammad Syafi'i, Ali (2009)
System protection is the important requirement in electrical power system. The using of protection system can avoid and prevent system from damaged. Electrical energy has caused dangers to human life and machine. Earth leakage circuit breaker (ELCB) is one from protection device that introduced to protect the system. This device is the brain of protection system that monitors input current from power line by it sensor Zero Current Transformer (ZCT), then sending the tripping signal to mechanical switch to disconnected system. ELCB is widely applied by consumer weather is for resident, factory, laboratory and also in power distribution. Because industrial operation requires protection of their Equipment from the lightning, short-circuit and also over-current, so the ELCB will serve the purpose as the protection of their system. This project will focused to improve the ability of current ELCB so that it have ability in identify fault, act accordingly, display the fault(permanent fault and temporary fault) and also re-close it back to normal condition.PIC will execute their instruction when different current from both of current transducer is exceed pre-determine value of sensitivity, 100mA. In this project PIC microcontroller will control and operate solid state relay which replacing the application of current mechanical switch.